European experience and prospects for the implementation of environmental certification in Ukraine’s hospitality sector - Bezsonnyi, V. L. (Man and Environment. Issues of Neoecology, 2025)
Purpose. This study analyzes the European experience in implementing environmental certification systems in the hospitality industry (ISO 14001, EU Ecolabel, Green Key) and identifies prospects for their adaptation in Ukraine. The focus is on the role of certification as a tool for sustainable management, ecological safety, and competitiveness of the HoReCa sector. Methods. The research applies system-analytical, comparative, statistical, and information-entropy approaches. Results. The data sources include EU Ecolabel, Green Key, and EMAS registers, Eurostat, Hotel Footprinting 2024, and scientific articles вгкштп 2020-2025. Quantitative indicators of energy and water consumption, CO₂ emissions, and certified hospitality facilities in EU countries were evaluated. Over 4200 European hotels hold Green Key certificates and around 900 have EU Ecolabel status, with the highest concentrations in Denmark, France, Spain, and Italy. ISO 14001 implementation reduces energy use by 15–25 %, water consumption by 20 %, and waste generation by up to 30 %. Major barriers for Ukraine include lack of incentives, insufficient environmental awareness, and limited availability of certified auditors. A national initiative “Green Hospitality UA” is proposed, based on EU Ecolabel principles and the Green Deal Policy. Conclusions. Environmental certification serves as an effective mechanism for ensuring ecological safety and sustainable development of hospitality enterprises. Integrating EU standards into Ukraine’s HoReCa sector will enhance resource efficiency, reduce environmental pressure, and improve its green reputation. Further research should focus on economic modeling of certification effects and integration into national tourism and environmental management policy.